Women's constructions of the 'right time' to consider decisions about risk-reducing mastectomy and risk-reducing oophorectomy - Howard A Fuchsia; Bottorff Joan L; Balneaves Lynda G; Kim-Sing Charmaine (BMC, 2010)
Abstract Background Women who are notified they carry a BRCA1/2 mutation are presented with surgical options to reduce their risk of breast and ovarian cancer, including risk-reducing mastectomy (RRM) and risk-reducing oophorectomy (RRO). Growing evidence suggests that a sub-group of women do not make decisions about RRM and RRO immediately following genetic testing, but rather, consider these decisions years later. Women's perspectives on the timing of these decisions are not well understood. Accordingly, the purpose of this research was to describe how women construct the 'right time' to consider decisions about RRM and RRO. Methods In-depth interviews were conducted with 22 BRCA1/2 carrier women and analyzed using qualitative, constant comparative methods. Results The time that lapsed between receipt of genetic test results and receipt of RRM or RRO ranged from three months to nine years. The findings highlighted the importance of considering decisions about RRM and RRO one at a time. The women constructed the 'right time' to consider these decisions to be when: (1) decisions fit into their lives, (2) they had enough time to think about decisions, (3) they were ready emotionally to deal with the decisions and the consequences, (4) all the issues and conflicts were sorted out, (5) there were better options available, and (6) the health care system was ready for them. Conclusions These findings offer novel insights relevant to health care professionals who provide decision support to women considering RRM and RRO.